Pengaruh Sistem Informasi Akuntansi Dan Pengendalian Internal Terhadap Efektivitas Penjualan Pada Perusahaan Dagang Di Kota Padang (Jurnal Kendali Akuntansi, 2024)
The purpose of this study was to determine and analyze the effect of accounting information systems and internal control on the effectiveness of sales at a trading company in the city of Padang. The population in this study were all trading companies in the city of Padang, amounting to 34 companies.Determining the number of samplesusing total sampling,then the number of respondents as a sample in this study were as many as 102 respondents, consisting of the Director/Manager, Supervisor and Treasurer. The data analysis technique used is multiple linear regression analysis and for hypothesis testing using statistical t test. The results showed that: the accounting information system variable had a partial significant effect on the effectiveness of sales at a Trading Company in Padang City, because it had a sig value. is 0.000 < 0.05. The internal control variable has a significant partial effect on the effectiveness of sales at a Trading Company in Padang City, because it has a sig value. its value is 0.019 < 0.05.